METAL-SULFATE SALTS FROM SULFIDE MINERAL OXIDATION - Jambor J.L.; Nordstrom D.K.; Alpers C.N. (My University, 2000)
“It is plain that almost all kinds of atramentum are made of Earth and Water. At first they were liquid and afterwards solid, and still they can be redissolved, by heat and moisture.” Albertus Magnus (1205–1280) Book of Minerals (transl. D. Wyckoff, 1967) The observation of “efflorescences,” or the flowering of salts, associated with periods of dryness in soils, in closed-basin lakes, in rock outcrops, and in mines and mine wastes has been noted since early antiquity. The formation of metal-sulfate salts, in connection with the mining of metals, was a phenomenon well known to the early Greek and Roman civilizations. Alum, most commonly potash alum KAl(SO4)2 · 12H2O, which is from the Latin alumen , was extensively mined and used by goldsmiths, dyers, paper manufacturers, and physicians in ancient civilizations. It forms from the oxidation of pyrite in shales and slates and from oxidation of sulfurous gases in geothermal areas. The Greeks and the Romans described stalactites of atramentum (soluble metal-sulfate salts) that formed within mines and along rock faces (Agricola 1546, 1556). Furthermore, the toxic effects of these salts on animals were also noted. For example, in De Natura Fossilium , Agricola (1546) stated “….I mention the congealed acid juice which usually produces cadmia . It is white, hard, and so acrid that it can eat away walls, grills and even destroy all living matter.” Cadmia is thought to be derived from the oxidation of zinc, cobalt, and arsenic sulfides, such as cobaltite. He goes on to say that “Pyrite, unless it contains sulphates, is either a golden or silver color, rarely any other, while cadmia is black, yellow brown, or gray. The former will cure gatherings while the latter is a deadly poison and will destroy any living substance. It is used …